Pengaruh Model Pembelajaran STAD Terhadap Keterampilan Shooting Bolabasket - Supriyatni, Deswita (Jurnal Master Penjas & Olahraga, 2023)
The purpose of this study was to determine the effect of the STAD learning model on students' basketball shooting skills. The method used in this study is the Experiment method with a Randomized Pretest-Posttest Control Group Design. The population in this study was grade VII students of SMPN 5 Cimahi, the sample was class VII / A students totaling 37 people for the experimental group and Class VII / B 38 people for the control group. The research instrument used was the basketball shooting skills test from Nurhasan (2013). Because the significance value < 0.05, Ho was rejected, so that at a 95% confidence level the result of the calculation was that the STAD learning model was more influential than the Direct Teaching Model on the basketball skills of grade VII junior high school students.